Mechanical Stretch Promotes the Osteogenic Differentiation of Bone Mesenchymal Stem Cells Induced by Erythropoietin - Yong-Bin He; Sheng-Yao Liu; Song-Yun Deng; Li-Peng Kuang; Shao-Yong Xu; Zhe Li; Lei Xu; Wei Liu; Guo-Xin Ni (Hindawi Limited, 2019)
Introduction. The effects of erythropoietin (EPO) on the behaviors of bone marrow mesenchymal stem cells (BMSCs) subjected to mechanical stretch remain unclear. This study was therefore aimed at establishing the dose-response effect of EPO stimulation on rat BMSCs and investigating the effects of mechanical stretch combined with EPO on the proliferation and osteogenic differentiation of BMSCs. Material and Methods. The proliferation and osteogenic differentiation of rat BMSCs were examined and compared using EPO with different concentrations. Thereafter, BMSCs were subjected to 10% elongation using a Flexcell strain unit, combined with 20 IU/ml EPO. The proliferation of BMSCs was detected by Cell Counting Kit-8, colony formation assay, and cell cycle assay; meanwhile, the mRNA expression levels of Ets-1, C-myc, Ccnd1, and C-fos were detected by reverse transcription and real-time quantitative PCR (qPCR). The osteogenic differentiation of BMSCs was detected by alkaline phosphatase (ALP) staining, and the mRNA expression levels of ALP, OCN, COL, and Runx2 were detected by qPCR. The role of the extracellular signal-regulated kinases 1/2 (ERK1/2) in the osteogenesis of BMSCs stimulated by mechanical stretch combined with 20 IU/ml EPO was examined by Western blot. Results. Our results showed that effects of EPO on BMSCs included a dose-response relationship, with the 20 IU/ml EPO yielding the largest. Mechanical stretch combined with 20 IU/ml EPO promoted proliferation and osteogenic differentiation of BMSCs. The increase in ALP, mineral deposition, and osteoblastic genes induced by the mechanical stretch-EPO combination was inhibited by U0126, an ERK1/2 inhibitor. Conclusion. EPO was able to promote the proliferation and osteogenic differentiation of BMSCs, and these effects were enhanced when combined with mechanical stretch. The underlying mechanism may be related to the activation of the ERK1/2 signaling pathway.